PERAN KEPALA MADRASAH DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK GURU (STUDI KASUS MI DARUL ISTIQAMAH AMAMOTU KECAMATAN SAMATURU) - Ikhwana ikhwana (IAI Al-Mawaddah Warrahmah Kolaka, 2020)
In order to make educational institutions more advanced, this is greatly influenced by the quality possessed by the head of madrasah in leading educators and education personnel. To achieve this, all madrasah principals must have a role in increasing their competence and developing their potential. Based on this, this study aims to explain the Role of Madrasah Principals in Improving Teacher Pedagogical Competence at MI Darul Istiqamah Amamotu, Samaturu District, Kolaka Regency. This study used a qualitative approach, with observation data collection techniques, interviews and documentation. In identifying data, using descriptive qualitative data analysis. In this study the researcher used three triangulations, namely triangulation of sources, methods and investigators. Source triangulation is used by comparing the results of observation data, interviews and documentation. Method triangulation is done by collecting circulating data such as observation, interviews and documentation. Investigator triangulation bends the data obtained by an informant with other informants. This study concludes that: 1) the role of the head of madrasah in improving the pedagogical competence of teachers at MI Darul Istiqamah Amamotu, namely: a) providing motivational encouragement to teachers, b) participating in various kinds of seminars, training and education and training, c) supervising teachers. 2) obstacles faced by the head of madrasah in improving the pedagogical competence of teachers at MI Darul Istiqamah Amamotu, namely: a) inadequate facilities and infrastructure, b) lack of financial support.